Aproximaciones historiográficas a la violencia en la Edad Media - Cecilia Devia (Medievalista)
This paper consists of a brief state of the question on the issue of violence in the Middle Ages, framed in the following coordinates of time and space: the late medieval Western Europe. In this opportunity, it takes into account only historiographical approaches. In the first place, are presented two moments that stand out in relation to violence in the Middle Ages, focusing mainly from the authors whose research has left more traces. Then, it discusses a selection of the most significant historiographical contributions published over the last twenty years or so.